2011
DOI: 10.1111/j.1524-4725.2011.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of Autologous Differentiated Adipocytes from Stem Cells Derived from Human Adipose Tissue

Abstract: The use of autologous differentiated adipocytes can be a safe and effective treatment for soft tissue defects, with relatively long-term maintenance of volume. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…*P < 0.05. trials. 15 The clinical applicability of hASCs spans all agegroups. Some studies have shown the effects of age on the proliferative and differentiation potentials of hASCs.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05. trials. 15 The clinical applicability of hASCs spans all agegroups. Some studies have shown the effects of age on the proliferative and differentiation potentials of hASCs.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were negative for the expression of the hematopoietic stem cell-associated markers CD34 and CD45 and the bone marrow-derived stem cell-associated marker STRO-1 [26]. Furthermore, genomic stability of ASCs was evaluated by karyotyping analysis and no evidence of tumor formation was observed in tumorigenicity study carried out with immunecompromised nude mice after repeated administration of cells.…”
Section: Preparation Of Ascsmentioning
confidence: 99%
“…Although, autologous fat grafts including ADSC [25] are in current clinical practice, their long-term graft retention [26] [27][28][29][30]. Alternatively, Kim and his coworkers were successful in transplanting the differentiating adipocytes from ADSC for treating depressed scar with up to 75 % success rate [31]. Developing strategies to reconstruct larger tissue defects, however, remains a formidable challenge.…”
Section: Soft Tissue Defectsmentioning
confidence: 99%